PROYECTO COLMENA Y SU INFLUENCIA EN EL DESARROLLO DE HABILIDADES SOCIALES EN LOS ESTUDIANTES DE 7MO AÑO EGB DE LA UEM JOSÉ DE SAN MARTÍN PERIÓDICO ACADÉMICO 2024-2025 - MENDOZA CORTEZ NATHALY SILVANA (2024)
This work focuses on evaluating the impact of the Colmena Project at the UEM José de San Martín, focused on 7th year EGB students. This project seeks to improve evaluate the implementation and effects of the Colmena Project in aspects such as extracurricular activities, project sustainability, teacher training and integration of curricular contents. A quantitative approach was used through student surveys. The sample included 27 7th year EGB students, selected through non-probabilistic sampling. The questions focused on identifying the types of extracurricular activities, the sustainability of the project, teacher training, and the integration of curricular content. The results revealed that 33.30% of the students participated in all extracurricular activities, with a significant preference for artistic (25.90%) and sports (22.20%). Regarding the sustainability of the project, 77.80% attributed the success to the active participation of the educational community. Regarding teacher training, 40.70% indicated that they focused on the development of socio-emotional skills. The integration of curricular contents was carried out mainly through interdisciplinary projects (59.30%). The Colmena Project managed to successfully integrate various extracurricular activities and encourage active participation of the educational community, this being crucial for its sustainability. However, it is necessary to strengthen the technological training of teachers and expand alliances with the private sector. The preference for interdisciplinary projects highlights the importance of a comprehensive approach to teaching. Recommendations include diversifying extracurricular activities, increasing funding, and promoting ongoing evaluations to adapt the project to the needs of the educational community.